Toxicological implications of pesticide use on snap beans in Sumapaz, Colombia - Cojocaru, A (International Center for Tropical Agriculture, 1990)
CIAT and Colombia`s national agricultural research institution, ICA, are involved in a collaborative study of the toxicological effects on farm workers and their families from using pesticides on snap beans. Between June and August 1989, blood samples were collected on three occasions from persons directly and indirectly (families) involved in snap bean cultivation in the Sumapaz area of Colombia. As an indicator of contamination by pesticides, the level of the enzyme cholinesterase was measured, using both the Lovibond and monotest methods. Preliminary results suggest the possibility of liver and kidney damage from excessive use of insecticides among male farm workers in Sumapaz. (AS)